Pengaturan Ketebalan Irisan Ubi Kayu untuk Meningkatkan Rendemen dan Karakteristik Beras Siger (Tiwul Modifikasi - Hidayat, Beni; Akmal, Syamsu; Surfiana, Surfiana (Jurnal Penelitian Pertanian Terapan, 2016)
Beras Siger (Tiwul Modification) is cassava-based rice analogues which adopts the Tiwulprocessing but with sightings (more uniform, brighter colors) and flavor better. Currently allof variant Tiwul processed with granulation method known as Beras Siger and known blackBeras Siger, yellow Beras Siger, and white Beras Siger. The main difference of processingbetween Beras Siger variants is slice thickness of cassava to be used as raw material. Theresearch aims to gain the optimal of slice thickness of cassava to increasing the yield andcharacteristics of Beras Siger. The study was conducted using a completely randomizeddesign with four treatments of slice thickness (0.3 ± 0.05 cm; 1.0 ± 0.1 cm; 2.0 ± 0,1 cm; and3.5 ± 0.5 cm), with five replications. The results showed that cassava slices with thickness of0.3 ± 0.1 cm will produce Beras Siger with lower yield (20.75 ± 0.48%), lower HCN content(3.82 ± 1.03 ppm) and lower starch content (78.03 ± 0.26%) but has more white color (57,80± 1,29%), higher crude fiber (5.84 ± 0.18%) and higher dietary fiber conte nt (14.20 ±0.39%) than other treatments.Keywords: thickness, yield, characteristic, Beras Siger, modification Tiwul